Potential hydraulic barrier performance of cyclic organic carbonate modified bentonite complexes against hyper-salinity. Issue 5 (October 2016) - Fehervari, A.; Gates, W.P.; Patti, A.F.; Turney, T.W.; Bouazza, A.; Rowe, R.K.
Abstract: The effect of adding glycerol carbonate (GC) or propylene carbonate (PC) to sodium (Na)-bentonite on the hydraulic performance of geosynthetic clay liners (GCLs) under hypersaline conditions is examined. Fluid loss (FL), swell index (SI) and solution retention capacity (SRC) measurements were carried out to compare the potential hydraulic performance of these two cyclic organic carbonates (COCs) as bentonite modifiers. A modified FL test enabled quantitative measurement of both the water retention characteristics of untreated and COC modified bentonites as well as calculation of hydraulic conductivity values. Tests under aggressively saline conditions (ionic strength, I ≥ 1 M of NaCl and ≥3 M of CaCl2 ) showed that at a mass ratio of 1:1 (GC to bentonite), the FL of a GC-Na-bentonite was ≈40–104 mL in NaCl and ≈61–91 mL in CaCl2 . This was about 10–20 mL and 70–200 mL, respectively, lower than that of a comparable PC-Na-bentonite (1:1 PC to bentonite) and untreated Na-bentonite. Greater swelling (SI) and greater solution retention capacity (SRC) was observed for the GC treated Na-bentonite compared to untreated Na-bentonite in all salt solutions, and for PC-Na-bentonite at high ionic strength of both NaCl and CaCl2 solutions, demonstrating the superior hydraulic barrier performance of COC-bentonites under severely saline conditions. Experiments conducted in flexible-wall permeameters with I = 3 M CaCl2 showed approximately one order of magnitude lower (∼10 −11 m/s vs ∼1.9 × 10 −10 m/s) hydraulic conductivity of GC treated bentonite cake compared to the k value of the untreated Na-bentonite cake. Calculated hydraulic conductivity from fluid loss tests estimated the measured values in a conservative way (overestimation).